THE INFLUENCE OF TEACHER DISCIPLINE AND CREATIVITY ON STUDENTS' LEARNING MOTIVATION IN MADRASAH - Wasilah, Nur; Abidin, Munirul (Managere: Indonesian Journal of Educational Management, 2022)
Teacher discipline and creativity are things that must exist in teachers. Teachers are always required to always be able to keep abreast of existing developments. Discipline and having high creativity will have an impact on students. According to several articles, creativity is needed in the world of education to support success. This study aims to determine the effect of teacher creativity and discipline on the learning motivation of class VIII students. This research uses quantitative research methods with correlational research types. with a research sample of 78 respondents who are students of MTsN 1 Malang City. Based on the results of partial and simultaneous testing, it was found that there was a positive influence between teacher creativity and discipline on student learning motivation. There is 20.4% teacher creativity affects student learning motivation and 25.5% teacher discipline affects student learning motivation.